2020
DOI: 10.1186/s13046-020-01580-4
|View full text |Cite
|
Sign up to set email alerts
|

ULK1 inhibition as a targeted therapeutic strategy for FLT3-ITD-mutated acute myeloid leukemia

Abstract: Background: In acute myeloid leukemia (AML), internal tandem duplication mutations in the FLT3 tyrosine kinase receptor (FLT3-ITD) are associated with a dismal outcome. Although uncoordinated 51-like kinase 1 (ULK1), which plays a central role in the autophagy pathway, has emerged as a novel therapeutic target for various cancers, its role in FLT3-ITD AML remains elusive. In this study, we evaluated the effects of ULK1 inhibition on leukemia cell death in FLT3-ITD AML. Method: We evaluated ULK1 expression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…In our present study, increased apoptosis of keratinocytes was observed by knockdown of ULK1 and treatment with ULK1 inhibitor but not by directly inhibiting autophagy with chloroquine or 3-MA, suggesting that ULK1 mediated apoptosis in an autophagyindependent manner. Indeed, previous literature indicates ULK1 inhibitors induced cell apoptosis via caspase activation and dysregulation of Bcl2/Bcl-xl (33)(34)(35). In agreement, we also observed a decrease in transcripts of Bcl2 and Bcl-xl in KCs treated with SBI (data not shown).…”
Section: Discussionsupporting
confidence: 92%
“…In our present study, increased apoptosis of keratinocytes was observed by knockdown of ULK1 and treatment with ULK1 inhibitor but not by directly inhibiting autophagy with chloroquine or 3-MA, suggesting that ULK1 mediated apoptosis in an autophagyindependent manner. Indeed, previous literature indicates ULK1 inhibitors induced cell apoptosis via caspase activation and dysregulation of Bcl2/Bcl-xl (33)(34)(35). In agreement, we also observed a decrease in transcripts of Bcl2 and Bcl-xl in KCs treated with SBI (data not shown).…”
Section: Discussionsupporting
confidence: 92%
“…Chen et al reported that in addition to ULK1, MRT-68921 can inhibit NUAK family SNF1-like kinase 1 (NUAK1), an anti-oxidant molecule, and eventually can exert effective cytotoxicity in various solid cancer cell lines 30 . Moreover, Hwang et al recently reported that both SBI-0206965 and MRT-68921 could induce degradation of internal tandem duplication mutations in the FLT3 tyrosine kinase receptor (FLT3-ITD) protein, thereby exerting cytotoxicity in FLT-ITD AML cells 31 . Thus, SBI-0206965- or MRT-68921-mediated inhibition of other kinases may also contribute to their cytotoxicity in leukemia cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous papers harbored the view that targeted inhibition of ULK1 contributed to the inhibition of tumor growth and metastasis in diverse cancers. [25][26][27] In CCA, it was documented that ULK1, targeted by miR-373, suppressed CCA cell apoptosis and promoted autophagy, thus promoting CCA development. 28 These views expressed that ULK1 was an oncogene in different cancers, suggesting that ULK1 inhibition might play the same effects with circ_HIPK3 knockdown.…”
Section: Discussionmentioning
confidence: 99%